Effects of Conflicts of Interest on Practice Patterns and Complication Rates in Spine Surgery. Issue 17 (1st September 2017) - Cook, Ralph W.; Weiner, Joseph A.; Schallmo, Michael S.; Chun, Danielle S.; Barth, Kathryn A.; Singh, Sameer K.; Hsu, Wellington K.
Abstract : Study Design: Retrospective cohort study. Objective: We sought to determine whether financial relationships with industry had any impact on operative and/or complication rates of spine surgeons performing fusion surgeries. Summary of Background Data: Recent actions from Congress and the Institute of Medicine have highlighted the importance of conflicts of interest among physicians. Orthopedic surgeons and neurosurgeons have been identified as receiving the highest amount of industry payments among all specialties. No study has yet investigated the potential effects of disclosed industry payments with quality and choices of patient care. Methods: A comprehensive database of spine surgeons in the United States with compiled data of industry payments, operative fusion rates, and complication rates was created. Practice pattern data were derived from a publicly available Medicare-based database generated from selected CPT codes from 2011 to 2012. Complication rate data from 2009 to 2013 were extracted from the ProPublica-Surgeon-Scorecard database, which utilizes postoperative inhospital mortality and 30-day-readmission for designated conditions as complications of surgery. Data regarding industry payments from 2013 to 2014 were derived from the Open Payments website. Surgeons performing <10 fusions, those without complication data, and those whose identity could not be verified through public records were excluded. Pearson correlation coefficients and multivariate regression analyses were used to determine the relationship between industry payments, operative fusion rate, and/or complication rate. Results: A total of 2110 surgeons met the inclusion criteria for our database. The average operative fusion rate was 8.8% (SD 4.8%), whereas the average complication rate for lumbar and cervical fusion was 4.1% and 1.9%, respectively. Pearson correlation analysis revealed a statistically significant but negligible relationship between disclosed payments/transactions and both operative fusion and complication rates. Conclusion: Our findings do not support a strong correlation between the payments a surgeon receives from industry and their decisions to perform spine fusion or associated complication rates. Large variability in the rate of fusions performed suggests a poor consensus for indications for spine fusion surgery. Level of Evidence: 3